Energy analysis of PV surfaces in BIPV applications - Molina-Tamayo Santiago; Yesid Moreno Andrés; Mendoza Felipe; Mesa Gabriel Espitia; Osorio- Gómez Gilberto (E3S Web of Conferences)
This paper studies the power generation performance of flexible solar panels at different radii of curvature for both concave and convex configurations. Its performance is evaluated horizontally and vertically to provide architects and designers with a reference of how power generation is impacted depending on the geometries selected for the design of facades or roofs. The study consisted of two phases, the first comprised a simulation to estimate the amount of energy a surface receives according to its geometry, orientation, location, and simulated period. The second phase corresponds to an experimental validation, in which five geometries were tested: two concave, two convex, and one flat as a baseline. The results indicate that, for horizontal configurations, curvature radii from 2.51 times the minimum radius allow adequate power generation to be maintained. In the concave configuration, 77.8% of the power generated by a flat PV module is achieved, while in the convex configuration, 80.21% is achieved. For vertical configurations, the convex geometry with minimum radius shows the best performance, exceeding the power of a flat module by 12.1%. The convex configuration with a radius of curvature of 2.51 times the minimum radius offers 81.14% of the flat reference power.